1997
DOI: 10.1002/(sici)1098-2361(1997)16:5<445::aid-zoo7>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Combined serial ultrasonography and fecal progestin analysis for reproductive evaluation of the female white rhinoceros (Ceratotherium simum simum): Preliminary results

Abstract: Ultrasonographic examinations of one multiparous 33‐year‐old female southern white rhinoceros (Ceratotherium simum simum) resulted in documentation of the animal's estrous cycle, elucidation of the timing of ovulation in relation to estrus, and ultrasonographic evidence of endometritis and associated early embryonic death. The preovulatory follicle was observed to change in shape from spherical to pear‐shape (n = 3) and to reach a mean follicular diameter of ˜30 mm (n = 4) in the 48 hr preceding estrus. An ovu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
91
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(105 citation statements)
references
References 14 publications
13
91
1
Order By: Relevance
“…As soon as P m reached baseline (follicular phase) values, follicles started developing. This is in contrast to other megavertebrae species such as giraffe (Lueders et al 2009) or rhinoceros (Radcliffe et al 1997) where follicles are constantly forming in all reproductive stages, even under the influence of a functional CL. In elephants, high P m levels appear to completely inhibit antral follicle formation.…”
Section: Luteogenesis In Elephantsmentioning
confidence: 58%
See 1 more Smart Citation
“…As soon as P m reached baseline (follicular phase) values, follicles started developing. This is in contrast to other megavertebrae species such as giraffe (Lueders et al 2009) or rhinoceros (Radcliffe et al 1997) where follicles are constantly forming in all reproductive stages, even under the influence of a functional CL. In elephants, high P m levels appear to completely inhibit antral follicle formation.…”
Section: Luteogenesis In Elephantsmentioning
confidence: 58%
“…The luteal cells of the acCLs may require the second LH peak to mature and become fully steroidogenically active. In Baringo giraffes (Giraffa camelopardalis rothschildi) and white rhinoceros (Ceratotherium simum simum) a time span of 5-6 and 7-9 days respectively has been reported from ovulation to first rise in progesterone levels (Radcliffe et al 1997, Lueders et al 2009). The short period from ovulation to increased P m concentrations in the Asian elephant supports the hypothesis that the acCL may initially be responsible for secreting this hormone while the ovCL contributes and maintains P m during the remainder of the luteal phase.…”
Section: Luteogenesis In Elephantsmentioning
confidence: 99%
“…Part of this lag may be attributable to the delay coinciding with the entero-hepatic circulation and faecal excretion of steroids, estimated to be 2-3 days in rhinocerotids (Hindle and Hodges, 1990;Heistermann et al, 1998), as well as to the delay of 2-3 days observed between onset of oestrus and ovulation in black rhinoceroses (Radcliffe et al, 2001). In addition, another interval probably occurs between ovulation and the subsequent increase in faecal progestagens, as has been described in white rhinoceroses (Radcliffe et al, 1997;Schwarzenberger et al, 1999).…”
Section: Discussionmentioning
confidence: 71%
“…This pathology has been identified in three captive white rhinoceros females, and the corresponding luteal phases, identified by faecal pregnane analysis, lasted about twice the average cycle duration (Radcliffe et al, 1997;Patton et al, 1999). These reports, combined with the fact that a history of mating followed by anoestrus without pregnancy in mares is indicative of early embryo loss (Youngquist, 1997), indicate that such pathology may be associated with type IIa cycles.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation